Microeconomics : - Baumol, William J. (Thomson / South-Western, 2005)
This textbook for an introductory undergraduate audience covers the standard material of microeconomics and presents it as if there is little theoretical controversy in the field. The CD-ROM contains self- testing exercises, graphing workshops, and video lectures (tied to a certain large news network).